Police act and police women: is Nigeria police force an agent of protection or violation of human rights? (2017)
The police are the specialist carriers of state power and have enormous powers. The police have the monopoly of legitimate use of force. The primary duties of the Nigeria police include the prevention and detection of crime, apprehension of offenders, preservation of law and order, protection of life and property and enforcement of all law Although police should ordinarily be considered an attractive career, the Nigeria women police face the challenge of inequality with their male counterparts, as a result of some provisions of the Police Act and its regulations, which limit women from the point of eligibility to join the force, right through other privileges of being a police.